FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN DIARE PADA BALITA DI PUSKESMAS SELURUH INDONESIA - Marpaung, Angelina Patricia Br; Pasaribu, Sumihar; Sinatra, Jadeny (Universitas Methodist Indonesia, 2019)
Background :Diarrhea is a bowel movement with a flabby stool consistency usually accompanied by an increase in frequency and if the stool weight is measured more than 200g per day. Diarrhea is declared acute, if it lasts less than 14 days. And declared persistent if it occurs between 14-28 days. Chronic diarrhea, if diarrhea occurs more than 4 weeks. In 2013 in Indonesian, diarrhea was one of the number two killers of children under five after ISPA( Acute Respiratory Infection) and around 10,000 per child died from diarrhea. The prevalence of diarrhea in basic health research 2013, diarrhea is spread across all age groups with the highest prevalence detected in children under five (1-4 years) namely 16,7%. This study aims to determine the factors that influence the incidence of diarrhea in children under five in public helath centers throughout indonesian. Method: This type of research uses the method of literature study or literature review with a maximum time span of journal publishing of 5 years from 2015 to 2020. The population in this study is mothers who have toddlers with diarrhea. Results: The results of this study indicate that the factors that influence the incidence of diarrhea in children under five in public healt centers throught indonesian based on the research variabels are nutrional status, immunization, exclusive breastfeeding, personal hygiene and environmental sanitation. It can be concluded that the most dominant factors affecting the incidence of diarrhea in infants are exclusive breastfeeding. The average previous study used a cross sectional study design with bivariate analysis statistical tests through the chi square test with different number of respondents and research locations. Suggestion: For the government, it is expected to increase counseling activities regarding diarrheal disease with the help of doctors or health center cadres, about the importance of clean and healthy living behavior.